Testing the susceptibility of kiwifruit (Actinida chinensis var. deliciosa) germplasm to Hemiberlesia lataniae. Issue 1 (2nd January 2019) - Hill, M. Garry; Zhuang, Qi Guo; Mauchline, Nicola A.; Sutherland, Paul W.; Stannard, Kate A.; Popowski, Elizabeth
ABSTRACT: This study demonstrates resistance in Actinidia chinensis var. deliciosa germplasm to the armoured scale insect Hemiberlesia lataniae, an important pest of kiwifruit in New Zealand. A bioassay was used to test the resistance of 120 vines from a germplasm collection in New Zealand. Fourteen of the vines were classified as resistant and five as moderately resistant. Eight crosses (two Susceptible (S) × Resistant (R); 1 R×S; 4 R×R; 1 S×S) were made from the original vines, and the resulting families examined for resistance. There were large differences in insect survival and size between the families. Three families from R×R parents and one from R×S parents had vines showing a hypersensitive-type response (plant cell death) to H. lataniae . There were large differences in the range of susceptibility to H. lataniae within families, suggesting that the trait is polygenic or that more than one resistance mechanism is present in the germplasm.